The chelation of colonic luminal iron by a unique sodium alginate for the improvement of gastrointestinal health - Horniblow, Richard D.; Latunde-Dada, Gladys O.; Harding, Stephen E.; Schneider, Melanie; Almutairi, Fahad M.; Sahni, Manroy; Bhatti, Ahsan; Ludwig, Christian; Norton, Ian T.; Iqbal, Tariq H.; Tselepis, Chris (Wiley, 2016)
Scope